2014
DOI: 10.5005/jp-journals-10005-1267
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Rehabilitation of Ocular Defect resulting from Pediatric Retinoblastoma

Abstract: ABSTRACT%Ocular defects result from tumor, congenital anomaly and external injury not only lead to serious impairment of function and esthetics but also make the patient psychologically disabled. Prosthetic rehabilitation attempts to restore these disfgurements may improve esthetic, level of function, general psychologic improvement and quality of life. This clinical report details an attempt to rehabilitate a pediatric patient who has undergone orbital enucleation resulting from retinoblastoma with the aid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Wearing prosthetic eyes is not only conducive to restoration of the child's appearance but can also effectively increase the patient's quality of life. 24 This study showed that the ocular prosthesis satisfaction of pediatric patients was associated with the parents' marital status, employment status, and annual family income. Other relevant studies on pediatric diseases have confirmed that the influences of socio-economic factors on the quality of life of pediatric patients were statistically significant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wearing prosthetic eyes is not only conducive to restoration of the child's appearance but can also effectively increase the patient's quality of life. 24 This study showed that the ocular prosthesis satisfaction of pediatric patients was associated with the parents' marital status, employment status, and annual family income. Other relevant studies on pediatric diseases have confirmed that the influences of socio-economic factors on the quality of life of pediatric patients were statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…Enucleation combined with ocular prosthesis implantation can reduce the degree of orbital collapse as much as possible and can reduce the incidence of facial deformity in growing children. Wearing prosthetic eyes is not only conducive to restoration of the child's appearance but can also effectively increase the patient's quality of life …”
Section: Discussionmentioning
confidence: 99%
“…Loss of the ocular globe during early childhood can have significant effects on the growth and development of the orbital area 9,10 . Anson et al.…”
Section: Figurementioning
confidence: 99%